1995
DOI: 10.4049/jimmunol.154.3.1491
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 reverses cytokine and immune abnormalities in Sezary syndrome.

Abstract: Cutaneous T cell lymphoma is a lymphoproliferative disorder typically characterized by skin invasion of clonally derived malignant CD4+ lymphocytes that phenotypically resemble mature Th cells. Sezary syndrome (SzS) represents an advanced form of cutaneous T cell lymphoma associated with generalized erythroderma and involvement of the peripheral blood by the malignant cell population. We have previously demonstrated aberrant cytokine production by PBMC in SzS characterized by increased IL-4 and deficient IL-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Even if there are dated findings of a reduced or suppressed IL-12 pathway in CTCL development, especially in SS patients [60,101,158], studies regarding the impairment of the IL-12/23 axis in psoriatic patients have shown no evidence of an increased risk of altered clinical history in developing CTCLs [159]. Still, IL12/23 therapies are recent, and more long-term data are needed to confirm these findings.…”
Section: Il-12 In Mf/ssmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if there are dated findings of a reduced or suppressed IL-12 pathway in CTCL development, especially in SS patients [60,101,158], studies regarding the impairment of the IL-12/23 axis in psoriatic patients have shown no evidence of an increased risk of altered clinical history in developing CTCLs [159]. Still, IL12/23 therapies are recent, and more long-term data are needed to confirm these findings.…”
Section: Il-12 In Mf/ssmentioning
confidence: 99%
“…Regarding the potential role of IL-12 as a treatment, there are some studies regarding the potential of the use of recombinant IL-12 in CTCLs: this is due to IL-12 being strongly able to induce Th-1 differentiation and conversion and suppressing Th-2 cytokines, making it a possible mechanism to treat MF and SS [60,138].…”
Section: Il-12 In Mf/ssmentioning
confidence: 99%
“…different TCL types and stages may be better suited for treatment with a therapeutic antibody versus a CAR-T), we also developed an allogeneic NK-cell based ADCC platform. As is generally known, patients with T cell malignancies often show increased opportunistic infections due to compromises in normal T cell and NK numbers and/or function [42][43][44][45][46][47][48][49][50][51][52][53][54][55] . We reasoned that allogeneic T cells with their more efficient transduction efficiency (relative to NK cell transduction) are suitable for CAR engineering directly, while donor NK cells could utilize infused therapeutic antibody via their Fc receptors as an alternative and complimentary therapeutic strategy.…”
Section: Cytokine Combinations For Allogeneic Hcar-vβ2 T Cell Expansi...mentioning
confidence: 99%
“…The immunosuppressive effects of malignant T cells can be reversed with skin-directed and systemic therapies (10)(11)(12). However, it is unclear whether this is mediated solely by depletion of malignant T cells or if therapies that independently augment the immune system toward a type 1 helper T cell (T h 1) bias have greater efficacy.…”
Section: Introductionmentioning
confidence: 99%